Commodity dynamism in the COVID-19 crisis: Are gold, oil, and stock commodity prices, symmetrical?. (December 2022) - Sadiq, Muhammad; Lin, Chia-Yang; Wang, Kuan-Ting; Trung, Lam Minh; Duong, Khoa Dang; Ngo, Thanh Quang
Abstract: The current research intends to examine the commodities' dynamism connection with stock prices under the COVID-19 crisis. DCC-GARCH modeling was applied to the data of Asian economies, including China, India, Sri Lanka, Bangladesh, and Pakistan to achieve the study objectives. The study's results indicated a significant connection between gold prices with stock prices and oil prices for all Asian stock markets. The results of the study constructs were symmetrical. In general, the connection grows with the frequency. The lowest frequency months contributed the most to the total relationship, followed by more than 12 months. Overall, gold and oil prices influence the Asian stock markets. These research findings can avoid contagion in times of economic uncertainty. This study also suggested policy implications for better decision-making of key stakeholders. Dynamic coefficient values were about 0.8 of β2 because nations' internal markets were more closely linked. There are also dynamic relationship factors between crude oil and foreign currency markets, where the correlations in India and China have always been around 0. Highlights: The study examines the commodities dynamism connection with stock prices during the COVID-19 crisis. The gold prices significantly linked with stock prices and oil prices in Asian stock markets. Higher metal prices may have a long-term detrimental effect on industrial production.